Karakter Kepemimpinan melalui Kegiatan Organisasi Siswa Intra Sekolah (OSIS) di SMA Negeri 4 Blitar - Anggita Fajerin, Wisnaya; Dwi Retnani Srinarwati; Suryanti Suryanti (Universitas Palangka Raya, 2025)
This study aims to describe the leadership character formed through the activities of the Student Organization (OSIS) at SMA Negeri 4 Blitar. The background of this research stems from the importance of building leadership character among the younger generation so that they can face the challenges of the times. As a student organization, OSIS plays a strategic role in instilling leadership values such as responsibility, independence, teamwork, integrity, and a sense of nationalism. To achieve this goal, the study employs a qualitative method with a descriptive approach. Data collection is carried out through observation, in-depth interviews, and analysis of documentation. The results of the study show that various programs implemented by OSIS, such as leadership training, class meetings, and both academic and non-academic competitions, effectively contribute to shaping students' leadership character. The study concludes that active student involvement in OSIS activities plays a crucial role in the development of leadership character within the school environment.